Anorectal malformations: history and current management - Baeza Herrera Carlos; Alarcón Quezada Victor; Nájera Garduño Heladio Marino (Instituto Nacional de Pediatría, 2014)
This study is a historical account of the ano-rectal malformations from the time it was considered as a structural defect susceptible of surgical correction, but in particular from the first formal attempts to carry it out. We were able to construct a chronologically ordered description taking into consideration the initial faltering attempts during the first third of the last century, the progress through a stage of assessment, so that by the end of the second third of the XXth century the most relevant discoveries were made, particularly in regard to the diagnosis and the definition of surgical management strategies. Finally, we point out the vicissitudes and the clinical investigations of Peña, the transcendental impact of his concepts on a skeptical and hostile surgical guild, his labor emigration to the U.S. hospitals and his growing reputation which accounts for his outstanding position.